2014
DOI: 10.1097/wnr.0000000000000251
|View full text |Cite
|
Sign up to set email alerts
|

Serum copper and zinc levels in individuals with autism spectrum disorders

Abstract: Trace elements play a critical role in the pathogenesis of autism spectrum disorders (ASD). The aim of this study was to investigate the serum levels of zinc (Zn) and copper (Cu) in Chinese children with ASD. Sixty patients (48 males, 12 females) diagnosed with ASD and 60 healthy sex-matched and age-matched control participants were assessed for serum Zn and Cu content at admission. The severity of ASD was also evaluated using the Childhood Autism Rating Scale (CARS) score. The results indicated that the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 24 publications
4
45
1
Order By: Relevance
“…Clinical data have previously established that mean serum Zn 2+ levels are significantly lower in children diagnosed with ASD compared to unaffected children and that there exist disturbances in Zn 2+ metabolism in patients diagnosed with ASD [10-12]. hDAT T356M is the first de novo DAT mutation found in a patient with ASD, and hDAT T356M functional deficits can partially be rescued by Zn 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data have previously established that mean serum Zn 2+ levels are significantly lower in children diagnosed with ASD compared to unaffected children and that there exist disturbances in Zn 2+ metabolism in patients diagnosed with ASD [10-12]. hDAT T356M is the first de novo DAT mutation found in a patient with ASD, and hDAT T356M functional deficits can partially be rescued by Zn 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of zinc have been measured in the infant hair of individuals with ASD [170], and in mouse models zinc deficiency during development leads to alterations in social behavior [171]. Disruptions in fetal copper homeostasis during brain development might contribute to ASD risk, with both elevated and decreased copper levels linked with autism [172174]. Employing a validated tooth matrix in a twin–cotwin design with monozygotic and dizygotic twins discordant for ASD, a study tested whether fetal and postnatal metal dysregulation increases ASD risk.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…A recent study suggests that increased levels of BPb in some children with ASD may trigger the production of serum anti-ribosomal P antibodies (Mostafa et al 2016b). It has been reported that ASD children often have a lower zinc (Zn)-to-copper (Cu) ratio in blood compared to healthy controls (Faber et al 2009, Li et al 2014, Crăciun et al 2016) and children with other neurological disorders (Macedoni-Lukšič et al 2015). It has been suggested that metallothionein (MT) dysfunction may occur as a cause of Hg accumulation in children with ASD, and the same dysfunction may also lead to Zn deficiency (Bjørklund 2013).…”
Section: Autoantibodiesmentioning
confidence: 99%